(untitled) (Journal of Engineering, 2011)
Electrochemical processes can provide valuable contributions to the protection of the environment through implementation of effluent treatment and production-integrated processes for the minimization of waste and toxic compounds. The performance of a novel pilot scale, batch re-cycled, flow-through cell, with stainless steel tubes bundle cathode in the removal of cadmium was investigated utilizing the potential results obtained from a batch mode. The studied electrochemical reaction was the cathodic reduction of Cd+2 using 0.5 M sodium sulphate as supporting electrolyte. The analyzed parameters were different initial Cd+2 concentrations (50,100, 200, 300, 400 ppm) and different electrolyte flow-rates (100, 200, 250, 300, 350 L/hr), the tubes number was 920 of 0.6 cm diameters. The overall empirical mass transfer correlation was found to be: Sh = 0.051 Re 0.859 Sc1/3 For 5 < Re < 20 and Sc = 649 Experimental results, analysis and correlations showed good performance of the cell and proved its adequacy in the removal of Cd+2 from simulated effluents.